Construction of Gender in Serbian Folk Religion - Marija Ristivojević (University of Belgrade, 2016)
Review of the book by Lidija Radulović. Pol/rod i religija. Konstrukcija roda u narodnoj religiji Srba. [Sex/Gender and Religion. The Construction of Gender in Serbian Folk Religion]. 2009. Beograd: Srpski genealoški centar i Odeljenje za etnologiju i antropologiju Filozofskog fakulteta